Aging experiments on the 20 Ah lithium‐ion polymer battery cells. Issue 2 (6th December 2021) - Liu, Yiqun; Liao, Y. Gene; Lai, Ming‐Chia
Abstract: The battery capacity loss and power degradation due to aging process is one of the concerns particularly in vehicle electrification. This paper investigates the effects of charging/discharging current C‐rate, operating ambient temperature, and cycling on the battery cell aging and aging progress. Two groups of aging experiments are conducted on the lithium‐ion polymer battery cells with 20 Ah capacities. The first group of aging tests investigate the effects of charging/discharging C‐rate and operating ambient temperature on the battery cell capacity after 300 cycles. After 300 cycles, the cell with 3 C‐rates charging/discharging cycling currents under 40°C ambient temperature retains 64.53% usable capacity, comparing to 94.61% usable capacity in the cell with 1 C‐rate charging/discharging cycling currents under 20°C. The second group of tests investigate the cell aging progress during 800 aging cycles under normal working conditions (1 C‐rate charging, 2 C‐rate discharging, and 25°C ambient temperature). The results show that the cell's usable capacity is 75.17% after 800 cycles. The internal resistance of the cell could be 0.0235 Ω after 300 cycles of 3 C‐rate charging/discharging cycles under 40°C, or as high as 0.034 Ω after 800 cycles of 1 C‐rate charging/2 C‐rate discharging cycles under 25°C.